DETERMINING PRODUCTS OR SERVICES PRICING ON MSME USING BREAK-EVEN POINT ANALYSIS METHOD - Utami, Yuni; Mubarok, Abdulloh (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The implementation of community empowerment programs always involves the participation of the community itself, which will later be integrated in a planning, implementation, control, and follow-up of the results of the program implementation such as its use and maintenance. With the development of the UMKM Community, there are problems that must be addressed in order to continue to develop and maximize the desired profit. One of the most important components in the problem of determining Profit is how they can determine the selling price and how to know the break-even point in producing the goods / services they market. Price is the exchange rate of goods or services which is stated in the unit of currency (rupiah). Price is an important marketing mix element in product marketing. MSMEs need to determine the selling price carefully. Setting prices too high will cause sales to decline, while setting prices too low can reduce the profits of MSMEs businesses. In a business, it can be concluded that fixed costs are constant expenses that must continue to be incurred, even though there is no production activity. Conversely, variable costs are only incurred by the business owner when carrying out the production of goods or services. Even though the two types of costs are different in one way or another, they must still be considered in running a business. The calculation of fixed costs and variable costs will help in determining the production costs that must be incurred in developing a business that is being run. Keywords: Determination of Product / Service Selling Prices, Raw Material Costs, Sales Commission Fees, Distribution Costs